Flannel Fabric Handicraft Training to Increase Entrepreneurial Interest in the Budi Lestari Community South Lampung - M Yasin al Arif; Ida Faridatul Hasanah; Muhammad Aridan; Muhammad Farhan Wibowo; Widya Oktarini (FOUNDAE (Foundation of Advanced Education), 2021)
Considering the increasing number of unemployed and the depletion of job vacancies, so many people are struggling with the economy. This flannel craft training aims to increase the interest in entrepreneurship of housewives in Purwosari hamlet. Flannel fabric is attracting attention and many fans among the public. This study uses the Participatory Action Research (PAR) method with 4 stages, namely planning, action, observation, and reflection. This flannel craft training lasted for 1 day and was attended by 40 participants from housewives from the Purwosari hamlet. The products made are brooches and keychains made of flannel. Interest in entrepreneurship increased from 39.3% or in the category of less interest to 90.1% or in the category of very interest. With this training, it is hoped that it can be a solution to the difficulties of the family economy and can create jobs through entrepreneurship